Caracterização fisiológica de genótipos de cana-de-açúcar e avaliação de seus desempenhos em condições de restrição hídrica - Santos, Júlio Renovato dos (2012)
Sugarcane is a C4 plant that can be grown in tropical and subtropical regions adapt to different soil types and climatic conditions, especially for its large and broad utility operation, and raw material for various products such as molasses, molasses, sugar and ethanol. However, the production of cane sugar is being affected by poor rainfall distribution and the reduction of presipitation in some regions. Thus, this study aimed to characterize (field capacity) and evaluate the performance of genotypes of sugar cane submitted to water restriction and rehydration, using physiological indicators. The study was conducted in two experiments conducted at the Department of Agricultural Engineering, Federal University of Sergipe (UFS) in the municipality of São Cristovão - SE. The seedlings used for both studies were transplanted at 45 days for vessels of 18 dm3. The first experiment was performed to characterize the genotypes, in which they were carried out at field capacity, rated to 154 days after the transplan, between 10:30 and 12h00h, analyzing the variables: chlorophyll a fluorescence, content of chlorophyll a, be total levels of proline, water potential, transpiration, leaf temperature and air humidity, when the main plant, stem diameter, leaf number and leaf area. The experimental design was randomized blocks with four treatments (genotype 698B, 712B, 260B and 3B), four replications and one plant as a plot. In terms of field capacity 3B genotype showed the highest levels of chlorophyll a, b and total, Fv / Fm, height of main stem and leaf water potential, especially also in number of leaves and leaf area. In relation to transpiration, leaf temperature and diameter, no difference was observed between genotypes. To determine the physiological performance under water restriction was interrupted irrigation for 154 days, being rehydrated, the media showed that the genotypes leaves only +1 or +2 expanded with at least 20% of the leaf green. The evaluations were performed every five days, and analyzed the following parameters: chlorophyll fluorescence, chlorophyll content, a, b and total levels of proline, water potential, transpiration, leaf temperature and air humidity, height of stem principal, number of leaves and leaf area of the main plant, dry weight and fresh shoot and root system, these last being held at the end of the experiment. The evaluations were performed between 10:30 and 12:00. The experiment was a factorial 4 x 9 (genotype 698B, 712B, 260B and 3B-nine evaluations during periods of water restriction and rehydration), four replications and one plant as a useful parcel Fluid restriction induced a decrease for the variables analyzed in all genotypes, and the 3B and 698B were less tolerant, and rehydrated in 10 and 15 days restriction. Already 260B and 698B were more tolerant, where they were rehydrated in 25 days of restriction. It was also noted that during the restriction of proline accumulation obtained for all genotypes, whereas 698B and 3B showed higher values compared with the other. After rehydration of this amino acid was reduced in all genotypes, so that no significant differences. As to recovery after rehydration, the highlights were the genotypes 260B and 3B. In general, the 260B had the highest tolerance with higher results for the variables analyzed.